Possible Involvement of Both Endoplasmic Reticulumand Mitochondria-Dependent Pathways in Thapsigargin-Induced Apoptosis in Human Neuroblastoma SH-SY5Y Cells - Yoshihisa Kitamura; Atsushi Miyamura; Kazuyuki Takata; Masatoshi Inden; Daiju Tsuchiya; Kumi Nakamura; Takashi Taniguchi (Elsevier, 2003)
Recently, it has been shown that endoplasmic reticulum (ER) stress causes apoptosis. However, the mechanism of the ER stress-dependent pathway is not fully understood. In human neuroblastoma SH-SY5Y cells, we detected a caspase-12-like protein that has a molecular mass (approximately 60 kDa) similar to that of mouse caspase-12. Thapsigargin, an inhibitor of ER-associated Ca2+-ATPase, induced the degradation of caspase-12-like protein. In addition, the degradation of caspases-9 and -3, cleavage of poly(ADP-ribose) polymerase, DNA fragmentation, and cell death were also observed. Pretreatment with phorbol-12-myristate-13-acetate, which induces the expression of antiapoptotic Bcl-2, inhibited thapsigargin-induced degradation of caspases-9 and -3, but not caspase-12-like protein degradation. A caspase inhibitor, benzyloxycarbonyl-Val-Ala-Asp(OCH3)-CH2F, inhibited the degradation of caspase-12-like protein, but not that of caspases-9 and -3. These results suggest that thapsigargin may induce the activation of both ER- and mitochondria-dependent pathways in human SH-SY5Y cells.